Exclusion of ethnic and other minority language nationals in education : a case of Lesotho's language in education policy - Matee, Lihotetso Gloria; Mokala, Ntsoaki Teresa; Moholei, Mpho Patricia; Mosola, Agnes Mpho; Phofu, Tiisetso (African Perspectives of Research in Teaching & Learning (APORTAL), 2023)
The exclusion of ethnic and other minority language nationals within the Lesotho educational system is a cause for concern. In the case of Lesotho, even though language policy as articulated in Curriculum and Assessment Policy (CAP) stipulates that mother tongue shall be used as a medium of instruction from Grade 1-3, it does not clarify as to which and whose mother tongue language. It is against this backdrop that the exclusion of ethnic and other minority language nationals in Lesotho education context is explored in this article. Qualitative research methodology was adopted for this study. This study unpacks the policy and how its implementation is difficult due to its exclusion of minority languages. The researchers used a case study research design to critically analyse the contents of Lesotho's language policy. The theoretical framework for this research predominantly draws on social constructionism, inclusive education and translanguaging. The study purposely selected four documents being CAP, Education Sector Strategic Plans of 2005-2015 and 2016-2026 and UNICEF 2016 document for analysis. A content analysis approach was used to analyse the data. The study reveals that in the context of Lesotho, ethnic and other minority language nationals are excluded in education. The education system of Lesotho is, therefore, exclusionist. It is recommended that there should be an ideal language policy to bridge the gap between home and school language(s).
Journal article published in African Perspectives of Research in Teaching & Learning Journal (APORTAL) Vol 7 (2) (2023)
Keywords: Curriculum and assessment policy; Ethnicity; Language policy; Minority group; Inclusive education; Translanguaging; Language policy; Inclusive education; Translanguaging (Linguistics); Curriculum-based assessment